Taking the commanding heights : BNBM's branding strategy - Yu, Chungling, (SAGE Business Cases., 2017)
BNBM is a state owned Chinese enterprise that manufactures Gypsum boards for the construction industry. This case examines how the brand management of BNBM and how this contributed to BNBM's sales growth.